Carbon nanodot-decorated alveolate N, O, S tridoped hierarchical porous carbon as efficient electrocatalysis of polysulfide conversion for lithium-sulfur batteries. (10th March 2019) - Zhong, Mei-e; Guan, Jindiao; Sun, Jingchun; Guo, Hui; Xiao, Zhubing; Zhou, Nan; Gui, Qingwen; Gong, Daoxin
Abstract: Rechargeable lithium-sulfur (Li−S) batteries are a significant energy-storage device owing to their eco-friendliness and high theoretical energy density. However, the shuttle effect of soluble polysulfides as well as the slow redox kinetics constrains the development of Li-S batteries. Herein, carbon nanodots-decorated alveolate N, O, S tridoped hierarchical porous carbon (a-NOSPC) material is synthesized via facile pyrolysis of tobacco stem. The coexistence of micropores, mesopores, and macropore in the hierarchical porous carbon are beneficial for physical accommodating/immobilizing active materials sulfur and rapid charge/ion transfer. Meanwhile, the N, O, S dopants provide rich electrocatalytic active site in chemical binding of polysulfides and their accelerated redox kinetics, thus guaranteeing high utilization on active materials. The resultant a-NOSPC/S cathode with an 2.7 mg cm −2 areal sulfur loading delivers a high reversible areal capacity of 2.90 mAh cm −2 at 0.1 C, maintaining 2.01 mAh cm −2 over 100 cycles, which is obviously superior to the most reported biochar-based electrodes. Our results provide an appealing avenue to the design of multifunctional sulfur host for advanced Li-S batteries. Graphical abstract: Image 1